The man with sweaty palm and soles - Jamani, Nurjasmine Aida; Jahn Kassim, Puteri Shanaz; Abdul Hadi, Azwanis (Academic of Family Physicians of Malaysia, 2018)
A 21-year-old male college student presented with excessive severe bilateral sweating of his palms and soles for the past 3 years, which has progressively worsened. His symptoms occur throughout the day but worsened during exams or whenever he felt anxious. The condition has caused him difficulty in holding objects and writing assignments, and has resulted in public embarrassment on several occasions. He has to wipe his hands with a handkerchief each time they sweat. He also needs to change his socks frequently. No other area of his body is similarly affected. He denied any associated symptoms, such as pungent body odour, changes in weight, fever, heat intolerance, or changes in bowel habits. He has no known medical illness and is not on any medication. Clinical examination revealed bilateral profuse sweating of the palms and soles. Other examinations were unremarkable.